Disasters and History The Vulnerability and Resilience of Past Societies - van Bavel, Bas (Cambridge University Press, 2020)
This monograph provides an overview of research into disasters from a historical perspective, making two new contributions. First, it introduces the field of 'disaster studies' to history, showing how we can use history to better understand how societies deal with shocks and hazards and their potentially disastrous outcomes. Second, we introduce historians to the topic of disasters and the field of disaster studies, and explicitly show the relevance of studying past disasters to better understand the social, economic, and political functioning of past societies.